La gestión del conocimiento operativo como punto de partida para la innovación de las organizaciones - Vigo Contreras, Temiss Antonio (2018)
The changing economic environment of the various productive sectors has empowered the use of knowledge as the main source of competitive advantage over traditional factors of production such as capital, labor and infrastructure. Therefore, knowledge must be managed efficiently and systematically in organizations in order to seek continuous improvement and competitiveness within their sector. This article synthesizes the existing theory on knowledge management based on the needs to innovate and improve aspects as varied in the operational level of an organization as the analysis of production processes, the review of the models of directing operations and the products or services to offer.